THE ANALYSIS OF SCHOOL EXPECTANCY INFLUENCE ON THE GROSS DOMESTIC PRODUCT AT THE LEVEL OF THE ROMANIAN ECONOMY - Delia, TESELIOS; Mihaela, SAVU; Ioana-Iulica, MIHAI (Strategii Manageriale)
At the level of the Romanian economy, Gross Domestic Product is one of the most important indicators. Analyzing its evolution we observe that the effects of the economic and financial crisis strongly influenced it, the year 2009 representing the proof that the Romanian economy was not stable. Along with the Gross Domestic Product variation, in this paper we present school life expectancy indicator, one of the components of the education indicator in the Human Development Index. The link between the two indicators is analyzed using regression for the period 2002-2012. The independent variable is considered school expectancy and the dependent variable is Gross Domestic Product. The calculations led to the conclusion that the variation of Gross Domestic Product is explained at a rate of 41% by the variation of school expectancy.